Strategi Public Relations KPU Jombang dalam Upaya Meningkatkan Partisipasi Pemilih Pemula pada Pilkada 2024 - Rindi Andriansah; Muhammad As’ad (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study discusses the Public Relations strategies employed by the Jombang General Elections Commission (KPU Jombang) in its efforts to increase the participation of first-time voters in the 2024 Regional Elections (Pilkada). The involvement of first-time voters is crucial for the sustainability of democracy and the legitimacy of the government. This research aims to identify the Public Relations strategies implemented by KPU Jombang, the challenges encountered, and the efforts made to address them. A descriptive qualitative method was used, with data collected through in-depth interviews. The findings indicate that KPU Jombang utilized media relations, face-to-face communication, events, and digital engagement strategies. The main challenges included limited human resources, time constraints, and low political literacy among first-time voters. To overcome these issues, KPU collaborated with schools, student organizations, and intensively utilized social media platforms. Using Grunig and Hunt’s Two-Way Symmetrical Model, this study recommends the importance of adaptive approaches tailored to the characteristics of first-time voters as a key to enhancing their participation in the regional elections.